Observer-based control for active suspension system with time-varying delay and uncertainty. (November 2019) - Wang, Kuiyang; He, Ren; Li, Heng; Tang, Jinhua; Liu, Ruochen; Li, Yangmin; He, Ping
Time-varying input delay of actuators, uncertainty of model parameters, and input and output disturbances are important issues in the research on active suspension system of vehicle. In this article, a design methodology involving state observer and observer-based dynamic output-feedbackH ∞ controller considering the above four factors simultaneously is put forward for active suspension system. First, the dynamics equations of active suspension system with time-varying delay are established according to its structure and principle, and its state equations, state observer, and observer-based controller considering time-varying delay, uncertainty of model parameters, and input and output disturbances are given separately. Second, the observer-based controller for quarter-vehicle active suspension system is designed in terms of the linear matrix inequality and the Lyapunov–Krasovskii functional, and the design problem of observer-based controller is converted into the solving problem of linear matrix inequalities. Finally, the gain matrix of observer and the gain matrix of controller are obtained by means of the developed controller and the model parameters of active suspension system; the MATLAB/Simulink model of this system is established; and three numerical simulation cases are given to show the effectiveness of the proposed scheme.